Hutang & Politik Penindasan - Eko Prasetyo (Unisia, 2001)
The dramatic economic crisis, which brought to the fall of Soeharto, can be considered as the turning point for the relation between Indonesia and several donor countries as well as international financial and monetary institutions. The eagerness of the country to release it self from the debt has led them to unconditionally follow the instruction of the mentioned financial and monetary institutions. Unfortunately, like in other various poor countries, their instruction does not promise the welfare of the people in the country. Therefore, the suggested solution is that Indonesian government has to maximize in eradicating corruption in all government bodies. Besides, it also has to optimize the performance of BPPN in, for example, selling assets, instead of persuading donor institutions for other bigger foreign debt.